Stabilized fermentation product of Cetobacterium somerae improves gut and liver health and antiviral immunity of zebrafish. Issue 120 (January 2022) - Xie, Mingxu; Xie, Yadong; Li, Yu; Zhou, Wei; Zhang, Zhen; Yang, Yalin; Olsen, Rolf Erik; Ringø, Einar; Ran, Chao; Zhou, Zhigang
Abstract: Probiotics are widely used in aquafeeds and exhibited beneficial effects on fish by improving host health and resisting pathogens. However, probiotics applied to aquaculture are mainly from terrestrial sources instead of the host animal. The purpose of the work was to evaluate the effects of stabilized fermentation product of commensal Cetobacterium somerae XMX-1 on gut, liver health and antiviral immunity of zebrafish. A total of 240 zebrafish were assigned to the control (fed a basal diet) and XMX-1 group (fed a basal diet with 10 g XMX-1/kg diet). After four weeks feeding, growth performance, feed utilization, hepatic steatosis score, TAG, lipid metabolism related genes and serum ALT were evaluated. Furthermore, serum LPS, the expression of Hif-1α, intestinal inflammation score, antioxidant capability and gut microbiota were tested. The survival rate and the expression of antiviral genes were analyzed after challenge by spring viremia of carp virus (SVCV). Results showed that dietary XMX-1 did not affect growth of zebrafish. However, dietary XMX-1 significantly decreased the level of serum LPS, intestinal inflammation score and intestinal MDA, as well as increased T-AOC and the expression of Hif-1α in zebrafish intestine ( p  < 0.05). Furthermore, XMX-1 supplementation decreased the relative abundance of Proteobacteria and increased Firmicutes and Actinobacteria. Additionally, XMX-1 supplementation significantly decreased hepatic steatosis score, hepatic TAG, serum ALT and increased the expression of lipolysis genes versus control ( p  < 0.05). Zebrafish fed XMX-1 diet exhibited higher survival rate after SVCV challenge. Consistently, dietary XMX-1 fermentation product increased the expression of IFNφ2 and IFNφ3 after 2 days of SVCV challenge and the expression of IFNφ1, IFNφ2 and MxC after 4 days of SVCV challenge in the spleen in zebrafish versus control ( p  < 0.05). In conclusion, our results indicate that dietary XMX-1 can improve liver and gut health, while enhancing antiviral immunity of zebrafish. Highlights: Dietary stabilized XMX-1 fermentation product didn't affect zebrafish's growth. Dietary XMX-1 fermentation product improved liver and gut health of zebrafish. XMX-1 fermentation product addition enhanced the antiviral immunity of zebrafish.